Cobalt(II) chloride catalyzed one-pot synthesis of α-aminonitriles - De, Surya K. (Beilstein Journal of Organic Chemistry, 2005)
A simple and efficient method has been developed for the synthesis of α-aminonitriles by a one-pot three- component condensation of aldehydes, amines, and potassium cyanide in acetonitrile in the presence of a catalytic amount of CoCl2 at room temperature.